Terpolymer acceptors based on bithiophene imide for all-polymer solar cells. (February 2021) - Sun, Weipeng; Wang, Junwei; Shi, Yongqiang; Wu, Ziang; Tang, Yumin; Feng, Kui; Woo, Han Young; Guo, Xugang; Zhang, Fei-Bao
Abstract: In order to improve light absorption and promote n-type performance, random copolymerization strategy was employed to afford a series of random terpolymer acceptors with acceptor1-acceptor2-acceptor3 (A1 -A2 -A3 ) type backbone. The polymers were synthesized from distannylated electron-deficient bithiophene imide monomer with various electron-deficient dibrominated co-monomers using the typical palladium-catalyzed Stille coupling condensation polymerization. Compared with their parent polymers, these A1 -A2 -A3 type terpolymer acceptors, particularly the dihexylthieno[3, 4- b ]pyrazine based terpolymer PBTP, can exhibit good miscibility, appropriate polymer crystallinity, and improved absorption in the long-wavelength region due to the incorporation of a third strong electron-withdrawing acceptor moiety thieno[3, 4- b ]pyrazine. Benefitting from the noncovalent S⋯N interactions, PBTP possessed a planar skeleton and achieved the highest power conversion efficiency (PCE) of 7.35% in the polymer series when serving as the acceptor material in all-polymer solar cells. These results indicate that the A1 -A2 -A3 type terpolymer acceptors should be promising candidates for developing high-performance all-polymer solar cells. Highlights: The New acceptor1-acceptor2-acceptor3 type backbone was designed to promote n-type performance. A random copolymerization strategy is an effective approach to tune organic semiconductor properties. All-polymer solar cells are prepared from these non-fullerene acceptors.